Intellectual property in the bio-sector research:: Applying patenting rules in a field with no definition of life - Soto, Stephany (2020)
Intellectual Property is a powerful legal and economic instrument. In our “knowledge economy”, patents are the preferred IP tool with special emphasis in the pharma – agro biotech industry. However, the growth of patents in the bio sector such as the pharma and agro fields, encounters many challenges. Life itself has not been defined yet. So, how can it be determined exactly when a living being, or a biological entity has been modified by itself or by human intervention, and thus address issues of patentability? Therefore, a researcher in the bio field cannot be alien to Intellectual Property, being the main actor in the revolution of the bio-pharma-agro sectors.